Ask your own question, for FREE!
Mathematics
OpenStudy (anonymous):

e^(2 x)-3 e^x-4=0

jhonyy9 (jhonyy9):

sign e^x =t than will get t^2 -3t -4=0 (t-4)(t+1)=0 t-4=0 t=4 t+1=0 t=-1 e^x =4 lne^x =lne^4 xlne=4lne x=4 e^x =-1 not is possibile

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!